PENGARUH PEMBERIAN PAKAN LENGKAP BENTUK PELET DIPERKAYA PROBIOTIK Lactobacillus salivarius TERHADAP PRODUKTIVITAS ITIK LOKAL PERIODE FINISHER - Sri Sumarsih; B. Sulistiyanto (Badan Perencanaan Pembangunan, Penelitian dan Pengembangan Daerah Provinsi Jawa Tengah, 2016)
The aim of the research was to evaluate the effect of complete feed pelet with addition probiotics Lactobacillus salivarius on feed efficiency and duck’s productivity in finisher period. The completely randomized design was been used on this research with 3 treaments and 5 replications. The treatments were R0 (complete feed pelet with 0% addition probiotics Lactobacillus salivarius), R1 (50% complete feed pelet with addition probiotics Lactobacillus salivarius), and R2 (100% complete feed pelet with addition probiotics Lactobacillus salivarius).The parameters were duck’s productivity (feed consumption, body weight gain and feed conversion). The results showed that given 100% pelet complete feed with addition of Lactobacillus salivarius probiotics (R2) significantly (p<0,05) increasing body weight gain and decreasing feed conversion. The conclusion was given 100% complete feed pelet with addition probiotics Lactobacillus salivarius (R2) can be used to improve duck’s productivity in finisher period.